Exploring ethnic differences in the post-university destinations of Russell Group graduates. (August 2018) - Lessard-Phillips, Laurence; Boliver, Vikki; Pampaka, Maria; Swain, Daniel
The high aspirations of British ethnic minorities are evident in their high rates of participation in higher education. However, some ethnic minority groups remain strikingly under-represented in the most selective universities, and recent studies have shown that university graduates from ethnic minority backgrounds are less likely than otherwise comparable white graduates to gain employment in a higher salary, graduate-level job after their degree. This is likely to be due partly to the effects on graduate labour market outcomes of subject studied and university attended. However, no study to date has explored the graduate labour market outcomes for ethnic minority students in the UK's most 'prestigious' universities, defined here as one of the 24 member institutions of the Russell Group. This article draws on data for recent graduates (2009–2013) from the Destinations of Leavers from Higher Education survey compiled by the UK's Higher Education Statistics Agency. We explore ethnic differences in attainment in five distinct graduate destinations (employment in professional occupations; further study; employment in non-professional occupations; inactivity; and unemployment), controlling for educational and social background. Our results suggest that ethnic minority graduates of Russell Group are less likely than their white counterparts to fare well in the labour market and are more likely to adopt a compensatory strategy of further educational investment, that is a strategy of entering postgraduate education to avoid short-term unemployment or underemployment in a non-graduate job. Our findings challenge a key assumption of the government's social mobility policy agenda that graduating with a good degree from a highly selective university enables ethnic minorities to realise aspirations for upward social mobility.